(untitled) - Metzgen, Fred (Oxford, 1990)
Electronic Data Interchange (EDI) is revolutionizing the way that business is conducted by replacing paper with electronic transactions exchanged between computer systems. This volume explains how to adopt EDI as a means of improving the business process and as a productivity tool
Keywords: Electronic data interchange,Trao đổi dữ liệu điện tử